An investigation into fishing boat optimisation using a hybrid algorithm. (1st November 2018) - Tezdogan, Tahsin; Shenglong, Zhang; Demirel, Yigit Kemal; Liu, Wendi; Leping, Xu; Yuyang, Lai; Kurt, Rafet Emek; Djatmiko, Eko Budi; Incecik, Atilla
Abstract: The optimisation of high-speed fishing boats is different from the optimisation of other displacement type vessels as, for high-speed fishing boats, the wave-making resistance decreases while the splashed resistance increases sharply. To reduce fuel consumption and operating costs in the current economic climate, this paper presents a fishing boat optimisation approach using a Computational Fluid Dynamics (CFD) technique. The RANS-VoF solver was utilised to calculate total resistance, sinkage and trim for a fishing boat in calm water. The Arbitrary Shape Deformation (ASD) technique was used to smoothly alter the geometry. A hybrid algorithm was presented to solve the complicated nonlinear optimisation problem. Herein, a Design of Experiments (DoE) method was applied to find an optimal global region and a mathematical programme was employed to determine an optimal global solution. Under the same displacement with the original hull, two optimisation loops were built with different design variables. After completion of the optimisation, two optimal hull forms were obtained. The optimisation results show that the optimisation loop presented in this study can be used to design a suitable fishing boat in the reduction of the total resistance in calm water. Highlights: A fishing boat optimisation study was conducted using CFD. The Arbitrary Shape Deformation technique was applied to alter the geometry. A hybrid algorithm was presented to solve the nonlinear optimisation problem. The results show a significant reduction in the total resistance.